The role of PI3K signaling pathway in Alzheimer’s disease - Pan, Jingying; Yao, Qi; Wang, Yankai; Chang, Suyan; Li, Chenlong; Wu, Yongjiang; Shen, Jianhong; Yang, Riyun (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is a debilitating progressively neurodegenerative disease. The best-characterized hallmark of AD, which is marked by behavioral alterations and cognitive deficits, is the aggregation of deposition of amyloid-beta (Aβ) and hyper-phosphorylated microtubule-associated protein Tau. Despite decades of experimental progress, the control rate of AD remains poor, and more precise deciphering is needed for potential therapeutic targets and signaling pathways involved. In recent years, phosphoinositide 3-kinase (PI3K) and Akt have been recognized for their role in the neuroprotective effect of various agents, and glycogen synthase kinase 3 (GSK-3), a downstream enzyme, is also crucial in the tau phosphorylation and Aβ deposition. An overview of the PI3K/Akt pathway's function in the pathophysiology of AD is provided in this review, along with a discussion of recent developments in the pharmaceuticals and herbal remedies that target the PI3K/Akt signaling pathway. In conclusion, despite the challenges and hurdles, cumulative findings of novel targets and agents in the PI3K/Akt signaling axis are expected to hold promise for advancing AD prevention and treatment.